PENGARUH KONSENTRASI NATRIUM BENZOAT DAN LAMA PENYIMPANAN TERHADAP MUTU MINUMAN SARI BUAH GANDARIA (Bouea macrophylla Griff) BERKARBONASI - Rence Aurelia Sumanik; Pamella Mercy Papilaya; Dominggus Rumahlatu (BIOPENDIX, 2017)
Background: Gandaria plants (Bouea macrophylla Griff) are one of the annual Maluku fruits which need to be cultivated because they are beneficial both economically and ecologically. This study aims to determine the effect of sodium benzoate concentration and storage time on Gandaria fruit juice (Bouea macrophylla Griff). Method: The type of research used in this study was an experimental type laboratory with experiments conducted in a closed room. This study uses ripe gandaria fruit in orange. This study used a completely randomized design method with 2 factors, namely, the concentration of sodium benzoate 200 ppm, 250 ppm, 300 ppm and storage time of 5 days, 10 days and 15 days. The parameters measured were vitamin C levels, total solid soluble and total acid levels. Results: The study showed that the concentration of sodium benzoate and storage time had an effect on vitamin C, total acid and total soluble solid. Whereas the interaction between the concentration of sodium benzoate and the length of storage gave a significant effect on total acid. Conclusion: The concentration of sodium benzoate and storage time have an effect on vitamin C, total acid and total soluble solid and the interaction between sodium benzoate concentration and storage time has a significant effect on total acid.